2022
DOI: 10.1159/000524759
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Ability of Systemic Inflammation Response Index for the Risk of Pneumonia in Patients with Acute Ischemic Stroke

Abstract: <b><i>Introduction:</i></b> Several studies have examined the crucial role of inflammatory indexes such as the ratio of monocyte and lymphocyte (MLR), systemic-immune-inflammation-index, and the ratio of neutrophil and lymphocyte (NLR) in stroke-associated pneumonia (SAP). However, the function of the systemic inflammation response index (SIRI) in SAP is not known. This study investigated whether SIRI at admission could predict the incidence of SAP in patients with acute ischemic stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…Consistent with other reports (16,37), the hospital stay length was prolonged in the SAP group. Studies have shown that stroke-related infections, especially pneumonia, are independently associated with poor functional prognosis after stroke.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with other reports (16,37), the hospital stay length was prolonged in the SAP group. Studies have shown that stroke-related infections, especially pneumonia, are independently associated with poor functional prognosis after stroke.…”
Section: Discussionsupporting
confidence: 92%
“…It was revealed that elevated SIRI is an independent indicator of poor prognosis in stroke (24)(25)(26), aneurysmal subarachnoid hemorrhage (28), and some tumors (29)(30)(31). Yan et al (16) found that higher SIRI was a significant risk factor for pneumonia in patients with acute ischemic stroke. A SIRI threshold of ≥2.74 was correlated with an increased incidence of SAP in patients with AIS (OR: 5.82, 95% CI: 4.54, 7.49, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inflammatory response increases rapidly after stroke onset and is strongly linked to the occurrence of SAP ( 18 ). Inflammatory biomarkers such as the NLR, SII, SIRI and PLR can reflect the state of systemic inflammation and the immune response ( 10 ). Neurological injury induced by the inflammatory response and the release of cytokines from immune cells results in the production of anti-inflammatory signals and inhibits cytokine production, ultimately inhibiting infection and preventing disease progression ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been used to predict poor outcomes following ICH and clinical outcomes of delayed cerebral vasospasm in patients with aneurysmal SAH ( 7 , 8 ). The systemic inflammation response index (SIRI) indicates the balance between the inflammatory response and immune status ( 9 ) and has good predictive power for SAP in acute ischemic stroke patients ( 10 ). There is evidence that the SIRI can predict aneurismal subarachnoid hemorrhage and tumors ( 11 ).…”
Section: Introductionmentioning
confidence: 99%